(untitled) (Bangladesh Journal of Medical Science, 2018)
In Bangladesh tuberculosis (TB) cases are fairly common but isolated hepatobilliary TB cases are extremely rare. Liver abscess due to TB without involvement of any other site causes diagnostic delay and can easily confuse with pyogenic or amoebic liver abscess or haepatocellular carcinoma. We present a case of a 44-years-old diabetic,normotensive male who presented with prolonged high grade fever with chill and rigor with tender hepatomegally. He was put on treatment for liver abscess but was not responding. Later on, histopathology was done and it turned out to be a case of tuberculous liver abscess. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.155-157